2011
DOI: 10.1148/radiol.11100699
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Angiogenesis Change Estimated by Using Diffuse Optical Spectroscopic Tomography: Demonstrated Correlation in Women Undergoing Neoadjuvant Chemotherapy for Invasive Breast Cancer?

Abstract: Purpose:To investigate if changes in tumor angiogenesis associated with complete pathologic response (pCR) or partial pathologic response (pPR) to treatment can be demonstrated by using diffuse optical spectroscopic (DOS) tomography. Materials and Methods:All participants in this prospective, HIPAA-compliant, institutional review board-approved study provided written informed consent. Eleven women with invasive breast carcinoma were imaged with DOS tomography prior to, during, and at completion of neoadjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 44 publications
3
55
0
Order By: Relevance
“…While this hypothesis was not studied explicitly, the apparently prognostic indication provided by Pre-TxHb T when combined with earlier pathological analysis (17) is consistent with the theory. Specifically, our earlier study of DOST versus pathologic immunohistochemical staining of biopsy specimens and resected surgical tissues in the same breasts showed that Hb T changes were directly correlated to changes in pathologically measured CD31 reduction in response to NAC (17). Here, CD31 is a pan-endothelial marker for identifying pre-existing blood vessel density and size.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…While this hypothesis was not studied explicitly, the apparently prognostic indication provided by Pre-TxHb T when combined with earlier pathological analysis (17) is consistent with the theory. Specifically, our earlier study of DOST versus pathologic immunohistochemical staining of biopsy specimens and resected surgical tissues in the same breasts showed that Hb T changes were directly correlated to changes in pathologically measured CD31 reduction in response to NAC (17). Here, CD31 is a pan-endothelial marker for identifying pre-existing blood vessel density and size.…”
Section: Discussionsupporting
confidence: 66%
“…After all treatment cycles were completed, DOST images of both breasts were obtained several days before surgery. Histopathological characteristics of the resected tissue were evaluated after surgery (17), and a complete (pCR) or incomplete (pIR) pathological response to NAC was determined and compared with the DOST results.…”
Section: Methodsmentioning
confidence: 99%
“…This dip in [HbT] (and in absorption at both wavelengths) followed by an increase suggests that optically measured early changes in the tumor region following treatment may not always correlate with final outcome, as has been shown in patients treated with chemotherapy. 40,41 An area of artifact was also seen in this image, and care was taken not to include this region in the image analysis, to avoid introducing errors to the calculated values.…”
Section: Discussionmentioning
confidence: 99%
“…The most robust and diagnostically significant NIRST parameter has been total hemoglobin concentration, Hb T , evidently because it is a surrogate for localized vascular density and associated angiogenic activity in cancers. 19,55 In prior studies, 29 MT conductivity has been highly correlated with NIRST Hb T in the breasts of women examined with both modalities, and hence, the addition of MR spatial information should similarly strengthen the diagnostic accuracy of MT. Further, MT offers some potential advantages over NIRST-namely, its noncontacting imaging array (eliminating poor/inconsistent sensor contact effects, albeit a coupling fluid is involved), and its much higher frequency signal amplitude and phase for image reconstruction (NIRST light is amplitude-modulated around 100 MHz to generate the detected signal amplitude and phase response) with much less signal attenuation (NIRST attenuation is also dependent on the source wavelengths of light).…”
Section: Introductionmentioning
confidence: 94%